AMIR TEMUR’S STATE AS A MODEL OF TURKIC STATEHOOD - Muqimjon Qirgizboev (Western European Studies, 2025)
This article analyzes, from the perspective of political science, the state-building experience of Amir Temur, who ruled over Mawarannahr in the XIV–XV centuries (1370–1405). The study examines Amir Temur’s efforts to establish a centralized state, to introduce principles of justice into public administration, and to unify and govern the population. Particular attention is given to the political mechanisms described in his work Tuzuklar (“Temur’s Code”), including the practice of making political decisions through various councils and consultative assemblies, the governance of society based on its division into social strata, and the implementation of justice-oriented diplomatic policies. These aspects are explored through historical examples aimed at identifying the outcomes of Temur’s administrative and diplomatic approaches.
Keywords: Amir Temur; principles of justice